Together: Towards Collaborative Living - Czischke, Darinka (TU Delft Open, 2023)
Collective living is on the rise in the Netherlands. Amid an unprecedented housing crisis, more and more people are turning to collective self-organization to provide community-oriented, sustainable and affordable housing. But why are these initiatives struggling to get off the ground? And what can we learn from other European countries? "Together: Space for Collective Living" is a collection of essays, data and case studies in the Netherlands and other European countries, building on the 2021 Project Together! Knowledge. The book addresses the following questions: what is the relevance of collective living, how can we realize these forms of housing, and who can use what actions to ensure that collective living can contribute to more sustainable cities and regions? The book illustrates the dilemmas and opportunities for a new paradigm about living together in the 21st century.